Exterior of the Mahanaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here are the plinth details of the east-facing elevation of the Mahanaleshwar Temple. Starting from the bottom to top, there are four mouldings in the plinth which consist of a plain kani moulding, graaspatti (a band of kirtimukha or face of glory), gajathara (band of elephants) and narathara (moulding containing human figures). The narathara has mithuna (amorous couples), maithuna, and deities in the depictions.